Sublimation‐like behavior of cardiac dynamics in heart failure: A malignant phase transition?. (26th July 2016) - Goldberger, Ary L.; Henriques, Teresa S.; Mariani, Sara
Abstract : An abrupt transition from sinus rhythm to atrial fibrillation (AF) is common in patients with chronic heart failure (CHF). We propose a conceptual framework for viewing this malignant transition in terms of a type of sublimation marked by the switch from highly periodic sinus interbeat interval dynamics characteristic of CHF to a state of random disorganization with AF. Sublimation of physical substances involves an increase in entropy via heat transfer. In contrast, the disease‐related sublimation‐like behavior involves a loss of information content, associated decreases in cardiac bioenergetic capacity and in multiscale entropy. © 2016 Wiley Periodicals, Inc. Complexity 21: 24–32, 2016